Retrospective review of 65 atrioesophageal fistulas post atrial fibrillation ablation - Jehaludi, Ameena (Indian Pacing Electrophysiol J, 2018)
BACKGROUND: Although a rare complication of catheter based ablation for atrial fibrillation (AF), atrioesophageal fistula (AEF) is a serious and fatal event [[1], [2], [3], [4], [5]]. Most reports of AEF are single cases or small case series. OBJECTIVE: The purpose of this study was to perform a comprehensive literature search of all published atrioesophageal fistula following catheter ablation for AF in order to identify the mortality rates associated with therapeutic modalities and suggest the most definitive management in reducing mortality. METHODS: A comprehensive literature review of reported observational cases of atrioesophageal fistula post catheter based ablation for atrial fibrillation was performed. RESULTS: Sixty-five cases of AEF post atrial fibrillation ablation were reviewed. The mean age was 55 years old. 73.8% (48/65) of the identified cases occurred in males (p < 0.001). Of the 65 cases, 13 underwent surgical radiofrequency ablation (RFA) and 52 underwent percutaneous RFA. Mortality resulted in 53.8% of those who underwent surgical RFA and in 55.8% of those who underwent percutaneous RFA (p = .888). The time range interval from procedure to onset of symptoms was 1–60 days. The most prevalent symptom, fever, occurred in 52 of the 65 cases, followed by neurological symptoms (n = 44). CT of the chest (n = 37), transthoracic echocardiogram (n = 21), and CT of the head (n = 18) were the preferred diagnostic modalities. Patients who underwent surgical correction with esophageal repair for treatment were more likely to survive, in comparison to patients who were treated with non-surgical interventions, such as antibiotic therapy, anticoagulation therapy or esophageal stenting. Of the total 34 patients who were treated surgically, 27 survived (79.4%). Of the total 31 patients who were treated non-surgically, only 2 survived (6.5%), reflecting significantly lower mortality with surgical versus non-surgical therapy (p < 0.001). CONCLUSION: Atrioesophageal fistula is an uncommon but potentially fatal complication of atrial fibrillation ablation. Patients who underwent surgical repair were twelve times more likely to survive than those treated with stenting, antibiotic therapy or no intervention. Based on the observation that patients are 12 times more likely to survive an AEF with surgery than without, the authors believe that prompt surgical correction of AEF should be considered as standard of care when dealing with this dreaded complication.